The Triple Bottom Line: Using Library Programming To Increase Sustainability Learning at an HBCU - Colbert-Lewis, Danielle M (East Carolina University)
The purpose of this study was to determine how the North Carolina Central University's James E. Shepard Memorial Library's Marketing Committee programs and events can provide opportunities for the university community to learn about sustainability issues pertaining to the triple bottom line: equity, economics, and the environment. To understand current issues related to sustainability on campus, an inventory and interviews were conducted. The inventory focused on how Shepard Library programs and events in previous years conceptualized sustainability. Interviews with students focused on their engagement with sustainability issues on campus and how Shepard Library programs and events can benefit students by including sustainability as a focus to inspire them to change their behavior or continue to benefit them as a result of the program or service. The study produced a resource guide for academic libraries and the university community to utilize and engage in learning about sustainability from multiple resources.
Keywords: triple bottom line; social equity; environment; economics; Libraries and community--North Carolina--Durham; Sustainable development reporting--North Carolina--Durham; Historically Black colleges and universities--North Carolina--Durham; James E. Shepard Memorial Library; Community and college--North Carolina--Durham